Latitudinal patterns and interannual variations of spring phytoplankton in relation to hydrographic conditions of the southwestern Atlantic Ocean (34°-62°S) - Olguin Salinas, Hector; Brandini, Frederico; Boltovskoy, Demetrio (Helgoland Marine Research)
In the present study, the distribution and abundance of microphytoplankton were assessed in the southwestern Atlantic Ocean from subtropical to polar waters (34°–62°S) in two austral springs with contrasting hydrographic conditions. Vertical profiles of open-ocean (ca. 54°W) samples (≥ 18 L filtered water) were performed in 20 stations (0–100 m) in 1994 and in 17 stations (0–50 m) in 1995. The latitudinal patterns of microphytoplankton groups, chlorophyll a, and diatom and silicoflagellate species were analyzed and compared with our previous study carried out in spring 1993 (30°–61°S). In the three springs, 197 diatom species, 173 of which showed mean relative density lower than 1 %, were identified. A consistent diatom biogeographic pattern emerged in the three consecutive springs, defining the Transitional (corresponding to the Brazil–Malvinas Current Confluence), Subantarctic and Antarctic Zones; and the Subantarctic and Polar Fronts, as their boundaries. This zonation reflects persistent features of this hydrographically heterogeneous region. The Polar Front was a weaker biogeographic boundary for diatom species than the Subantarctic Front. Interannual changes in diatoms (mainly in species richness, dominant species and degree of dominance of species with different ecological affinities) were detected. The Transitional Zone, which is one of the most hydrographically variable regions of the world ocean, showed the highest changes in the diatom assemblage, reflecting a colder spring in 1995 and a warmer spring in 1994 than normal (1993). These changes agreed with differences reported for 1993–1995 in large-scale hydrographic conditions, including a widespread diversity decrease in 1995 due to a weaker influence of subtropical waters. Fil: Olguin Salinas, Hector. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y ...